Towards lab-in-a-fiber : a literature review - Lin, Yisen (2014)
Over the years, the importance and significance of fast diagnosis tools and tests, particularly in the medical field, has influenced interests in the development of point-of-care (PoC) devices and subsequently to lab-on-chip (LoC) technology for PoC applications. This paper discusses and explores the potential development of photonic crystal fibers, as an analogous form of LoC for PoC use, termed as lab-in-a-fiber (LiF). The combined advantages of LoC and optofluidics as well as its working mechanism in LiF will be discussed in depth. LiF, if successfully translated and implemented, is expected to be useful for PoC applications.